Isolation and characterization of mammalian orthoreovirus from bats in the United States. Issue 2 (22nd January 2023) - Wang, Liping; Zheng, Baoliang; Shen, Zhenyu; Nath, Nirmalendu Deb; Li, Yonghai; Walsh, Timothy; Li, Yan; Mitchell, William J.; He, Dongchang; Lee, Jinhwa; Moore, Susan; Tong, Suxiang; et al.
Abstract: Mammalian orthoreovirus (MRV) infects many mammalian species including humans, bats, and domestic animals. To determine the prevalence of MRV in bats in the United States, we screened more than 900 bats of different species collected during 2015–2019 by a real‐time reverse‐transcription polymerase chain reaction assay; 4.4% bats tested MRV‐positive and 13 MRVs were isolated. Sequence and phylogenetic analysis revealed that these isolates belonged to four different strains/genotypes of viruses in Serotypes 1 or 2, which contain genes similar to those of MRVs detected in humans, bats, bovine, and deer. Further characterization showed that these four MRV strains replicated efficiently on human, canine, monkey, ferret, and swine cell lines. The 40/Bat/USA/2018 strain belonging to the Serotype 1 demonstrated the ability to infect and transmit in pigs without prior adaptation. Taken together, this is evidence for different genotypes and serotypes of MRVs circulating in US bats, which can be a mixing vessel of MRVs that may spread to other species, including humans, resulting in cross‐species infections.